Prevalence And Risk Factors of Drug-Related Issues Found in Prescription Evaluations Conducted by Pharmacies - Alamri, Mohammed Abdullah; Alqasimi, Asma Abdulghani; wan, Ahmed Yosef; Almansouri, Ahmed Saad; Alkathiri, Assaf Essa; Banjar, Mutaz Fuad; Akbar, Asmaa Jamal; Almalki, Sami Salem; Bahmdan, Rahaf Hisham; ALSURAYHI, MAJED JAMEEL (Journal of Ecohumanism, 2025)
Background: Drug-related problems (DRPs) are a significant concern in healthcare, interfering with treatment outcomes and posing risks to patient safety. Older adults are particularly vulnerable due to polypharmacy and potentially inappropriate medications (PIMs). Community pharmacy-led medication reviews offer a proactive approach to identifying and mitigating DRPs, yet their full potential remains underutilized. This study aimed to investigate the prevalence and types of DRPs identified in prescription evaluations, assess PIM use among older adults, and explore associated risk factors. Methods: A cross-sectional study was conducted across 150 community pharmacies, involving 1,000 patients . Pharmacists performed comprehensive medication reviews, documenting DRPs, patient demographics, medication regimens, and resolution strategies. Data were analyzed using descriptive statistics, logistic regression, and subgroup analysis for older adults, with PIMs classified using validated criteria. Results: DRPs were identified in 41.5% of patients (47% at the drug level), with inappropriate drug choice, adherence issues, and dosage errors being the most common. Older adults exhibited higher DRP prevalence, driven by polypharmacy (mean 12±3 drugs) and PIM use (37.5%). Key risk factors included advanced age (adjusted OR 1.8 for ≥85 years), polypharmacy (OR 1.6 for ≥15 drugs), and patient knowledge gaps (OR 1.4). Medication plans reduced DRP risk in older adults (OR 0.75). Conclusion: Community pharmacy medication reviews effectively identify DRPs, particularly in older patients with complex regimens. Targeted interventions addressing polypharmacy, knowledge gaps, and PIM use are critical to enhancing medication safety. Pharmacists play a pivotal role in mitigating DRPs through systematic reviews and collaborative care. Future research should standardize DRP assessment and expand to underrepresented populations.